A multi-deformable bodies solution method coupling finite element with meshless method in sheet metal flexible-die forming - Yuan, Binxian; Wang, Zhongjin (Procedia engineering, 2017)
In this paper, a multi-deformable bodies solution method which includes both sheet metal elastoplastic deformation and bulk deformation of pressure-transmitting medium (PTM) in sheet metal flexible-die forming was proposed. The elastoplastic deformation of sheet metal was analyzed with finite element method (FEM), and the bulk deformation of PTM was analyzed with a meshless method, called element-free Galerkin method (EFGM). Aiming at the coupled deformation characteristics and strong nonlinear features between sheet metal/FEM and PTM/EFGM, a node-to-point contact method based on slave-master concept was employed to treat the frictional contact between these two deformable bodies. A numerical example of sheet metal flexible-die forming was presented to demonstrate the effectiveness of the proposed method.